1993
DOI: 10.1002/ajim.4700230205
|View full text |Cite
|
Sign up to set email alerts
|

A mortality study of cobalt production workers: An extension of the follow‐up

Abstract: The follow-up of a cohort of workers employed in an electrochemical plant producing cobalt and sodium, previously studied from 1950-1980, has been extended from 1981-1988. The standardized mortality ratio (SMR) for all causes of death was 0.85 (95% confidence interval [CI] = 0.76-0.95, 309 observed) for the whole cohort, and 0.95 (95% CI = 0.83-1.08, 247 observed) for the subcohort of workers born in France. With regard to lung cancer mortality among cobalt production workers, which is the main objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 7 publications
(5 reference statements)
0
18
0
Order By: Relevance
“…In an electrochemical plant where workers were exposed to cobalt alone, no increased risk of lung cancer could be detected after a follow-up period of more than 35 years (1950 -1988; standardized mortality ratio [SMR], 0.85) [Moulin et al, 1993]. In contrast, a mortality study in workers from the hard metal industry followed from 1956 to 1989 showed a significantly increased mortality from lung cancer (SMR, 2.13) that was related to the intensity of exposure (SMR, 5.03 in the highest exposure group).…”
Section: Introductionmentioning
confidence: 99%
“…In an electrochemical plant where workers were exposed to cobalt alone, no increased risk of lung cancer could be detected after a follow-up period of more than 35 years (1950 -1988; standardized mortality ratio [SMR], 0.85) [Moulin et al, 1993]. In contrast, a mortality study in workers from the hard metal industry followed from 1956 to 1989 showed a significantly increased mortality from lung cancer (SMR, 2.13) that was related to the intensity of exposure (SMR, 5.03 in the highest exposure group).…”
Section: Introductionmentioning
confidence: 99%
“…Cases of HMD have been reported among workers in all phases of CTC production (Bech et al, 1962;Coates and Watson, 1971;Sjo¨gren et al, 1980;Davison et al, 1983;Sprince et al, 1984Sprince et al, , 1988Meyer-Bisch et al, 1989;Cugell et al, 1990;Figueroa et al, 1992;Fischbein et al, 1992), which may be due to exposures to tungsten carbide particles in association with cobalt particles (Lasfargues et al, 1992(Lasfargues et al, , 1995Lison and Lauwerys, 1990, 1994, 1995Lison et al, , 1996. In humans, excess lung cancer has been observed among hard metal workers exposed to CTC dusts (Lasfargues et al, 1994;Moulin et al, 1998;Wild et al, 2000;Lison et al, 2001), but not among cobalt production workers exposed to cobalt alone (Moulin et al, 1993). In vitro and in vivo studies indicate that the genotoxicty of cobalt in the presence of tungsten carbide is greater than either component alone (Anard et al, 1997;Van Goethem et al, 1997;Lison et al, 2001;De Boeck et al, 2003a, b;Mateuca et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…With the rise of modern epidemiology in the 1950s, several important industry-based studies were conducted in the United Kingdom during the 1950s and the 1960s. (12) and cobalt (13).…”
Section: Historical Perspective Of Occupational Cancer Research In Eumentioning
confidence: 99%